Nanostructured MnO2 Films for 3D Micro‐Supercapacitors: From New Insights of the Growth Mechanism to the Fine Tuning of Areal Capacitance Values. Issue 3 (1st March 2023) - Bounor, Botayna; Asbani, Bouchra; Douard, Camille; Deresmes, Dominique; Stiévenard, Didier; Roussel, Pascal; Favier, Frederic; Lethien, Christophe; Brousse, Thierry
Abstract : Maximizing the electrochemical performance of 3D micro-supercapacitors based on pseudocapacitive films is crucial for powering the next generation of miniaturized IoT devices. The films have to be nanostructured, must conform the 3D template, and have uniform deposition. To study the growth mechanism of nanostructured MnO2 films obtained by a pulsed electrodeposition method, in situ Atomic Force Microscopy methods operating in liquid mode, Scanning Electron Microscopy, and electrochemical characterization techniques were used. The impact of ON and OFF times during the pulsed electrodeposition process was investigated. The deposition mechanism in Volmer Weber Island growth mode provided some guidelines to tune the deposit morphology to enhance the electrochemical performance of the 3D electrode based on nanostructured MnO2 films.